2015
DOI: 10.1097/ccm.0000000000001264
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Therapy Benefits Septic Mice With Adrenal Insufficiency But Harms Septic Mice Without Adrenal Insufficiency*

Abstract: This study demonstrates that corticosteroid treatment benefits mice with adrenal insufficiency but harms mice without adrenal insufficiency. This study also reveals that inducible corticosteroid has both immunosuppressive and immunopermissive properties, suppressing interleukin-6 production, promoting phagocytosis of immune effector cells, but not inducing peripheral lymphocyte apoptosis. These findings support our hypothesis that corticosteroid is an effective therapy for a subgroup of septic patients with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…It was reported that adrenal SR-BI is required for the production of inducible glucocorticoid (iGC) in sepsis in a relative adrenal insufficiency mouse model generated by adrenal transplantation 38 . Adrenal transplantation has few limitations such as technique issue and the cut-off of the neuron and chromaffin cells communication.…”
Section: Mice With Adrenal Insufficiency Were Susceptible To Clp-indumentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that adrenal SR-BI is required for the production of inducible glucocorticoid (iGC) in sepsis in a relative adrenal insufficiency mouse model generated by adrenal transplantation 38 . Adrenal transplantation has few limitations such as technique issue and the cut-off of the neuron and chromaffin cells communication.…”
Section: Mice With Adrenal Insufficiency Were Susceptible To Clp-indumentioning
confidence: 99%
“…Another data showed that basal plasma cortisol>20μg/dl and Δmax≤9μg/dl resulted in significantly high mortality (82%) in septic patients 53 . In animal studies, mice with adrenal insufficiency were very susceptible to sepsis-induced death as well 35,37,38,54 . These suggest that adrenal functions were strongly correlated with sepsisrelated mortality.…”
Section: Adrenal Insufficiency Worsens the Outcomes Of Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…SRBI whole-body knockout mice show much more susceptible to septic death. Macrophage SRBI via TLR4 signaling modulate immune response during sepsis (16) and adrenal SRBI deficiency mice fail to generate inducible corticosteroid (iCS) leading to aberrant inflammatory response during sepsis (17). We have reported that hepatic SR-BI significantly protects against CLP induced sepsis using Scarb1 I179N mice which is a mutant SR-BI mouse model with 90% depletion in hepatic SR-BI.…”
Section: Introductionmentioning
confidence: 99%
“…A recent animal study showed that corticosteroid treatment is only beneficial in septic mice with an absolute adrenal insufficiency, while it harmed the mice without such adrenal insufficiency (52). Besides the importance of accurately determining 'who' to treat, it also should be further investigated 'how' to best treat these patients.…”
Section: E Boonen and G Van Den Berghementioning
confidence: 99%